PENGARUH PELATIHAN DAN PENGALAMAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. INDONESIA POWER UJP PLTU BARRU - Multazam; Muhammad Rusydi; Syarifuddin Sulaiman (Jurnal Ilmiah Manajemen Emor (Ekonomi Manajemen Orientasi Riset), 2024)
The aim of this research is a type of quantitative research with the aim to know the impact of training and work experience on the productivity work of employees of PT. Indonesia Power UJP PLTU Barru. The type of data used in this study is quantitative data obtained from the shared questionnaire and related to the program being studied. In this study, the data sources used in data collection include primary data and secondary data. The research instruments used in this study used the likert scale method. Then the result of the research data used statistical calculations through the application SPSS. The result of the study showed that the training margin (X1) of labour productivity (Y) is 0,005< 0,05 and the tvalue 2,920 > ttable 1,667 with a positive regression coefficient value of 0,221, which means there is a positive and significant influence on employee productiveness. While work experience (X2) of work productivity (Y) is <0,001 < 0,05 and tvalue 5,704 > ttable 1,667 with a positive regression coefficient value of 0,647 which means there is a positive and significant influence between work experience on employee work productiveness.